Motivația intrinsecă și extrinsecă în achiziția limbii române ca limbă străină în mediul online - Ana Mihaela ISTRATE (ACROSS, 2022)
This study focuses on the most recent challenges that language teachers have been facing in the last year and a half with the onset of the health crisis caused by the Covid19 pandemic. It addresses the most important issues related to synchronous and asynchronous online teaching, highlights some of the most important theories in online language teaching, and looks at the intrinsic and extrinsic motivation that drives young people to continue learning online. The most important conclusion is related to the importance of that linking element, which can bring about a change of mentality, not only for the teachers involved in teaching Romanian as a foreign language, but especially in terms of how young people enrolled in the programme are able to embrace change. Thus, the level of involvement of the teacher is very important, being able to push the educational process to the point of creating a virtual environment comfortable and interesting enough to attract students, to determine cognitive processes, to initiate the desire for knowledge and development. Last but not least, the article turns its attention to how students have adapted to language teaching in the online environment with the help of the Microsoft Teams teaching platform, which has proven to be extremely important as a teamwork tool, allowing the development of modern projects, interactive presentations and lectures that can be recorded and viewed afterwards. In this way, an educational space can be developed that is capable of supporting a much greater number of interactive activities, supported by visuals, while providing immediate feedback to the student.